Adrenoceptor‐related decrease in serum triglycerides is independent of PPARα activation. (28th June 2019) - Konstandi, Maria; Kypreos, Kyriakos E.; Matsubara, Tsutomu; Xepapadaki, Eva; Shah, Yatrik M.; Krausz, Kristopher; Andriopoulou, Christina E.; Kofinas, Aristeidis; Gonzalez, Frank J.
Abstract : Adrenoceptor (AR)‐linked pathways belong to the major components of the stress response system and are associated with the pathophysiology of diseases within the spectrum of metabolic syndrome. In this study, the role of adrenoceptor stimulation in serum triglyceride (TG) regulation in mice was investigated. For this purpose, α1 ‐ARs were activated with phenylephrine (PH) and β1/2 ‐ARs with isoprenaline (ISOP). Both AR agonists markedly reduced serum TG levels independently of PPARα activation. These drugs also significantly activated the hormone‐sensitive lipase in the white adipose tissue indicating increased mobilization of TGs in this tissue. In addition, PH and ISOP up‐regulated Lpl, Nr4A, Dgat1, Mttp, Aadac and Cd36 genes, critical in TG regulation, whereas the observed decrease in serum TG levels was independent of the hepatic very low‐density lipoprotein (VLDL)‐TG secretion. Interestingly, PH and ISOP also inactivated the hepatic insulin/PI3k/AKT/FoxO1 signaling pathway, holding a critical role in the regulation of genes involved in TG synthesis. Taken together, the findings of the present study indicate that stimulation of α1 ‐ and β1/2 ‐ARs markedly reduced serum TG steady‐state levels as a result of alterations in TG synthesis, uptake, transport, hydrolysis, metabolism and clearance, an effect induced by PPARα independent mechanisms. Abstract : Drugs stimulating α1 ‐ or β1/2 ‐adrenergic receptors (AR) can efficiently reduce serum triglycerides (TG) by inducing various genes in the liver and white adipose tissue (WAT) that regulate TG hydrolysis, transport, metabolism, and clearance in a PPARα‐independent mechanism. β1/2 ‐AR–induced hormone‐sensitive lipase (HSL) phosphorylation at Ser660 in the WAT appears to play a central role in the isoprenaline‐mediated mobilization of TGs from the liver and their reduction in serum.